Study protocol and overview of the Kasama Study: Creating a comprehensive, community-based system for preventive nursing care and supporting successful aging - Tomohiro Okura; Taishi Tsuji; Kenji Tsunoda; Naruki Kitano; Ji-Yeong Yoon; Mahshid Saghazadeh; Yuki Soma; Jieun Yoon; Mijin Kim; Takashi Jindo; Shaoshuai Shen; Takumi Abe; et al. (Japanese Society of Physical Fitness and Sports Medicine, 2017)
This study protocol introduces the Kasama Study, a mid-sized longitudinal study of health, fitness, and physical activity in older people. The study is a challenging research project that discusses the future of the system for preventive nursing care and for supporting successful aging in Japan. In May 2008, we began the Kasama Study with an exercise program of preventive nursing care for community-dwelling older adults. As of March 2016, we have conducted six study projects: 1) the Kasama health checkup for longevity, 2) an all-round exercise class, 3) the volunteer and the circle, 4) an exercise class for men only, 5) an exercise class for improving cognitive and physical function, and 6) the Kasama Iki-iki checklist survey. We describe each project in detail in the present study protocol.